Pengaruh Relief Topografi Terhadap Daerah Prospek Nikel Laterit Kecamatan Bahodopi Kabupaten Morowali Provinsi Sulawesi Tengah - Astuti, Sri Epi; Anshariah, Anshariah; Anwar, Habibie; Djamaluddin, Djamaluddin (Jurnal of Mining Insight, 2023)
Nickel laterite deposit is a result of weathering processes of  ultramafic rocks which carry Ni-Silicate. Generally the deposit is found from tropical to subtropical climates. The aim of this research was to find out the influence of the ground slope to the thickness zone of the nickel laterite based on the cross-section of the drill hole. The research method was to create the cross-section nickel laterite. The data ware obtained from assay data, coordinate, drilling points distribution, and cross-section of the drill hole. From cross-section of the drill hole, the data regarding the level of Ni and Fe were obtained. From the hole id 5A_0171, the lowest Ni level for limonite was 0.19%, and the highest level was 1.17% and for the Fe level, the lowest was 32.13% and the highest was 49.84% with the depth ranging from 0 to 18 metres. The lowest Ni level for the saprolite was 0.79% and the highest was 2.04% whereas for the Fe  level, the lowest was 9.97% and the highest was 15.77% with the depth ranging from 18 to 25 metres. The lowest Ni level for the bedrock was 0.29% and the highest was 0.56% whereas for its Fe level, the lowest was 6.91% and the highest was 8.67% with the depth ranging from 25 to 27 metres. The concluding data for the sloppy areas from the steep to slightslopes was that the limonite zone tended to follow the surface morphology pattern with the thickening occurrence in the steep slopes however the saprolite zone did not follow the surface morphology but it became thick in the steep slopes.